Palliative Care in Emergency General Surgery Patients: Reduced Inpatient Mortality And Increased Discharge to Hospice. Issue 7 (July 2021) - Baimas-George, Maria; Yelverton, Sam; Ross, Samuel W.; Rozario, Nigel; Matthews, Brent D.; Reinke, Caroline E.
Background: Admissions due to emergency general surgery (EGS) are on the rise, and patients who undergo emergency surgery are at increased risk of mortality. We hypothesized that utilization of palliative care and discharge to hospice in the EGS population have increased over time and that this is associated with a decrease in inpatient mortality. Methods: Using the 2002-2011 nationwide inpatient sample and American Association for the Surgery of Trauma-defined EGS diagnosis codes, we identified patients ≥18 years old with an EGS admission. Demographics, hospitalization characteristics, mortality, use of palliative care services, and discharge to hospice were queried. All Patient Refined-Diagnosis Related Group risk of mortality was used to categorize those with an extreme likelihood of dying (ELD). Multivariable logistic regression was used to investigate the association between palliative care consult and discharge to hospice. Results: Of the included patients, 0.3% received palliative care and 0.2% were discharged to hospice. Over time, rates of palliative care and hospice discharge increased while inpatient mortality decreased. In the 4% of patients with ELD, 3% received palliative care, 5% were transitioned to hospice care, and 22% suffered inpatient mortality. Controlling for patient characteristics, utilization of palliative care services was associated with increased odds of discharge to hospice compared to inpatient mortality (OR = 1.78 all patients and OR = 2.04 for ELD). Conclusions: Despite the known increased risks associated with emergency surgical diagnoses, palliative care services remain infrequently utilized in the EGS population. This may be an opportunity for lessening suffering, improving patient-concordant care and outcomes, and reducing nonbeneficial and unwanted care.